Future hydrological alterations in the Mekong Delta under the impact of water resources development, land subsidence and sea level rise - Cochrane, T.A. (2020)
Depending on hydrological characteristics of each region (river-dominated, transitional or tidal), the influence of each potential driver may vary. The operation of proposed hydropower dams would change river-dominated upper floodplain’s water levels by 26 to 70% and −0.8 to −5.9% in the dry and wet season respectively, but the impact diminishes throughout the floodplains. In the wet season, the upper Vietnamese Delta changes from a transitional stage to a river-dominated stage, and localized water infrastructure development in the upper delta has the greatest effect on water levels in the region. Land subsidence combined with sea level rise could have the greatest future influence on flooding in the delta if current rates are extrapolated. Sustainable water management strategies are thus necessary to mitigate changes in the floodplains and delta and increase resilience to sea level rise and land subsidence.